The Effect of Online Gamification Learning on Students' Motivation and Students' Writing Descriptive Text - Rodiatul Hasanah Bani Muhsin; Imam Nur Aziz (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
Online gamification learning is an imaginative methodology that expects to build manufacturing clients' commitment and motivation. The inspiration driving this assessment was to investigate the impacts of the utilization of online gamification learning on students’ motivation and students' writing descriptive text. The study was conducted at MTs. Mambaus Sholihin Gresik in class VIII I. To know whether online gamification learning is effective, the researcher utilized a pre-experimental method in which the information was tried by a statistical formula of t-test. The consequence of the exploration is the mean of the pre-test was 66.3810 and the mean of the post-test was 80.2143. The questionnaire appeared that students who agree with the method of online gamification learning have motivated and helped them in writing descriptive text. It can be concluded that the students' motivation and students’ accomplishment in writing descriptive text is improved when they are educated by online gamification learning.